A template method for preparing hydrogel photothermal materials

Through the template method and oxidation modification treatment, hydrogel photothermal materials with high efficiency photothermal absorption and energy conversion performance were prepared, which solved the problems of complex preparation process and high cost in the prior art. They are suitable for seawater desalination and high salt Wastewater treatment.

CN116120746BActive Publication Date: 2025-02-11HUBEI MEICHEN ENVIRONMENTAL PROTECTION CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211533708.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-02-11
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

The prior art has problems such as complex reaction process, harsh conditions, long preparation time and high cost when preparing hydrogel photothermal films.

Method used

The hydrogel photothermal material is prepared by the template method. By improving the detailed composition and detailed morphology structure of the hydrogel photothermal material, the oxidation modification treatment in the oxidation solution can enhance the photothermal absorption rate and pass through the surface microscope. Structural design improves energy utilization efficiency.

Benefits of technology

It realizes efficient photothermal absorption and energy conversion, reduces preparation cost and time, improves the stability and application breadth of materials, and is especially suitable for seawater desalination and high-salt wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116120746B_ABST
    Figure CN116120746B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of solar evaporation technology, and discloses a template method for preparing a hydrogel photothermal material, wherein the preparation method is to use a template with a concave array structure on the surface, firstly subject a Kevlar hydrogel solution to template method shaping, then solidify its surface micromorphology by a phase inversion method, and then add it to an oxidation solution of MPD and CuSO4 for solution oxidation, so as to prepare a hydrogel photothermal material by modification. The present invention improves the detailed composition and detailed morphology structure of the hydrogel photothermal material, artificially manufactures the surface microstructure, and cooperates with the oxidation modification treatment in the oxidation solution, so as to efficiently enhance the photothermal absorption rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar evaporation, and more specifically, relates to a template method for preparing a hydrogel photothermal material. Background Art

[0002] Since water evaporation only occurs on the surface, the traditional overall evaporation method has serious heat loss. The interface evaporation technology concentrates the heat on the water-air interface, greatly improving the energy utilization efficiency. In the process of treating seawater with solar interface evaporation technology, solar energy collection and water vapor generation both occur on the water-air interface, and then the water vapor condenses and is collected as fresh water.

[0003] Hydrogel is a special dispersion system that is formed by cross-linking hydrophilic polymer chains to form a three-dimensional network structure, and the gaps in the structure are filled with a large amount of water. Common polymer hydrogels include polyvinyl alcohol (PVA), polyacrylamide (PAM), chitosan (CS) and gelatin. Kevlar fiber is a high-performance fiber material developed by DuPont in the United States in the 1960s. It is a para-aromatic polyamide organic fiber with advantages including high strength, low density, good high temperature stability, and chemical corrosion resistance. The specific gravity of Kevlar fiber is only 1.44g / cm 3 , only 1 / 5 of steel and 1 / 2 of fiberglass, but its strength is 5 times that of steel and 2 times that of fiberglass.

[0004] Chinese patent CN113603913A discloses a photothermal film, which contains carbon nanotubes and chitin, and the chitin and carbon nanotubes are connected to wrap the surface of the carbon nanotubes. Although it also discloses a photothermal film based on a hydrogel film, it still has problems such as complex reaction process, harsh conditions, long preparation time and high cost. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a template method for preparing hydrogel photothermal materials, wherein the detailed composition and detailed morphology of the hydrogel photothermal materials are improved, the surface microstructure is artificially manufactured, and the oxidation modification treatment in the oxidation solution is combined to efficiently enhance the photothermal absorption rate; and the hydrogel has a certain self-cleaning ability, and has the performance of a membrane, and can be applied to water treatment. In addition, the present invention has a simple structure and high energy utilization efficiency, and can be widely used in the fields of seawater desalination, high-salt wastewater treatment, etc. The template used in the preparation process is reusable and has high durability, and the preparation process is simple and the raw material cost is low.

[0006] To achieve the above object, according to one aspect of the present invention, a method for preparing a hydrogel photothermal material is provided, characterized in that it comprises the following steps:

[0007] (1) pouring a completely dissolved Kevlar hydrogel solution onto a template and leveling it to obtain a Kevlar hydrogel film prototype; wherein the surface of the template has a concave array structure;

[0008] (2) soaking the Kevlar hydrogel film prototype in pure water so that it is completely in contact with water and gradually undergoes phase transformation and solidifies into a film;

[0009] (3) peeling the solidified Kevlar hydrogel film from the template to obtain a Kevlar hydrogel film having a corresponding protrusion array structure on the surface;

[0010] (4) placing the Kevlar hydrogel film obtained in step (3) into an oxidizing solution for oxidative modification, thereby obtaining an oxidatively modified Kevlar hydrogel film, which is a hydrogel photothermal material; wherein the oxidizing solution is a mixed aqueous solution of copper sulfate and metaphenylenediamine (MPD).

[0011] As a further preferred embodiment of the present invention, in step (4), the oxidizing solution is obtained by mixing an aqueous solution of m-phenylenediamine and an aqueous solution of copper sulfate; wherein the mass percentage concentration of the aqueous solution of m-phenylenediamine is 1-10%, and the mass percentage concentration of the aqueous solution of copper sulfate is 1-10%;

[0012] The mixing is carried out in a volume ratio of 1-10:1 between the m-phenylenediamine aqueous solution and the copper sulfate aqueous solution.

[0013] As a further preferred embodiment of the present invention, in step (4), the time for oxidative modification in the oxidative solution is 10-30 minutes.

[0014] As a further preferred embodiment of the present invention, in step (1), the template is obtained by 3D printing, and the material of the template is an alloy; the mass percentage concentration of the Kevlar hydrogel solution is 0.1-2%;

[0015] In the step (2), the soaking time is 10-60 minutes.

[0016] As a further preferred embodiment of the present invention, in step (1), the Kevlar hydrogel solution is obtained by dissolving Kevlar fibers in a mixed solution of KOH aqueous solution and DMSO;

[0017] In the step (1), the leveling is performed by scraping off excess solution with a scraper, and the thickness of the hydrogel solution left on the template is 100-1000 μm.

[0018] As a further preferred embodiment of the present invention, in the step (1), the size of the projection of a single recessed array structure unit on the template surface on the plane where the template surface is located is 0.5-2 mm;

[0019] Preferably, in step (1), the surface of the template has a recessed hemispherical array structure; the projection of a single recessed hemispherical array structure unit on the plane where the template surface is located is a circle, and the diameter of the circle is 0.5-2 mm; accordingly, the Kevlar hydrogel film obtained in step (3) is a Kevlar hydrogel film with a hemispherical protrusion array structure on the surface.

[0020] According to another aspect of the present invention, the present invention provides a hydrogel photothermal material prepared by the above method.

[0021] According to another aspect of the present invention, the present invention provides the use of the above hydrogel photothermal material as a photothermal material.

[0022] As a further preferred embodiment of the present invention, the application is specifically the application in photothermal evaporation using light energy; preferably, the light energy is solar energy.

[0023] As a further preferred embodiment of the present invention, the photothermal evaporation is specifically used for seawater desalination or high-salinity wastewater treatment.

[0024] The above technical scheme conceived by the present invention is compared with the prior art, because the solar thermal evaporation material in the present invention is prepared by using cheap and high-performance Kevlar hydrogel after template shaping and oxidation modification. The Kevlar hydrogel solution is first shaped by the template method, and then its surface micromorphology is solidified by the phase inversion method, and then added to the oxidation solution of MPD and CuSO4 for solution oxidation, so as to be prepared by modification. On the one hand, Kevlar has the advantages of good toughness, high strength, low density, good high temperature stability, and chemical corrosion resistance; on the other hand, the modified solar thermal evaporation material has low cost and high-efficiency thermal evaporation performance, which is very suitable for practical applications.

[0025] The flat film (FS) produced by the traditional film-making method has a high light scattering rate, which reduces the energy conversion efficiency. The present invention uses a template with an array structure design on the surface (which can be produced by 3D printing) to artificially create some microstructures on its surface during the film-making process, and cooperates with oxidation modification to improve the photothermal evaporation rate and energy conversion efficiency.

[0026] The present invention uses a template with a concave array structure on the surface, solidifies the Kevlar hydrogel into a film with a certain surface microstructure through a phase inversion method, and then makes it a photothermal material with stable structure and high performance through oxidation modification, which can be particularly applied to photothermal evaporation. The content of chemical groups such as hydroxyl and carboxyl groups on the surface of the membrane is increased through modification of the CuSO4 and m-phenylenediamine (MPD) oxidation system, which is helpful for water transmission.

[0027] Specifically analyzed, the present invention can achieve the following beneficial effects:

[0028] (1) The present invention selects Kevlar hydrogel material as the substrate, which has better light and heat stability and antifouling performance than ordinary hydrogel materials. Kevlar is easy to obtain as a raw material, low cost and good effect. The material is light and the processing process is simple, which is convenient for production and storage. At the same time, the oxidized polymer generated on the surface is very stable and can be directly stored in an air environment later.

[0029] (2) The photothermal material of the present invention can effectively improve the photothermal evaporation efficiency by combining the surface microstructure with the oxidation modification treatment, and the energy conversion efficiency is also increased accordingly. The present invention utilizes the oxidation reaction of m-phenylenediamine and copper sulfate to load a layer of poly-m-phenylenediamine complex on the photothermal material and form a stable polymer, so that the material as a whole has a higher light absorption capacity. The light absorption capacity is improved by utilizing the synergistic effect of the material microstructure and the poly-m-phenylenediamine polymer formed on the surface of the material.

[0030] (3) The photothermal material in the present invention can be particularly applied to photothermal evaporation. By using the interfacial evaporation technology, the present invention can not only obtain a higher amount of fresh water, but also harvest salt crystals. It can be further used to construct solar evaporation and salt crystal collection devices based on the separation of the light-receiving surface and the evaporation surface, and convert high-salt wastewater or seawater into fresh water and salt crystals through photothermal evaporation. For example, photothermal evaporation films of different sizes can be prepared by changing the size of the template, which can be laid on foam and other supporting layers to assemble into solar evaporation devices to meet the needs of different application scenarios.

[0031] The present invention artificially manufactures a specific surface microstructure on a macro scale (especially millimeter scale) through a template method, thereby increasing the specific surface area of ​​the photothermal evaporation film; through oxidation modification, its surface roughness is increased on a micro scale (nanoscale), the light absorption area is increased, and the photothermal conversion efficiency is increased; at the same time, the surface hydrophilicity is increased through oxidation solution modification, the water transmission rate is enhanced, thereby comprehensively improving the overall photothermal conversion rate.

[0032] In summary, the present invention has low cost, simple process, high photothermal conversion efficiency, and can be widely used in the fields of seawater desalination, high-salt wastewater treatment, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a physical picture of the unoxidized Kevlar hydrogel film obtained between Comparative Example 1 and Example 1 of the present invention; wherein, the flat structure Kevlar film corresponds to Comparative Example 1, and the hemispheric structure Kevlar film corresponds to Example 1.

[0034] Figure 2 is a scanning electron microscope image of the surface of the Kevlar hydrogel film before and after oxidation modification in Example 1 of the present invention; wherein, Figure 2 (a) corresponds to before oxidation modification, Figure 2 (b) in the figure corresponds to the oxidation modification; Figure 2 The scale bars in the graphs represent 1 μm.

[0035] Figure 3 It is a comparison chart of the evaporation rates of pure water under 1 sun intensity for photothermal materials of different morphologies of comparative example 1 and embodiment 1 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0037] Based on the present invention, using a template with a concave array structure (the specific shape of the concave can be pre-set), it can be first scraped into shape by a traditional film scraping method, and then the surface microstructure can be fixed by a phase inversion method; then, MPD and CuSO4 are used for oxidation modification, and oxides are loaded on the surface micro-nanostructure, and the obtained hydrogel photothermal material can effectively improve the photothermal conversion efficiency as a whole. In addition, before the template is used, a layer of release agent (such as PDMS coating) can be coated first, so that the hydrogel film can be demolded faster.

[0038] In addition, a template having a recessed array structure on its surface can be prepared by a 3D printing process, and the projection size of a single array unit on the plane where the template surface is located is in the millimeter or micron order.

[0039] The template used in the following embodiments is a template having a hemispherical concave array structure on the surface obtained by a 3D printing process, and the projection of a single hemispherical concave array unit on the plane where the template surface is located is circular. The Kevlar solution used (i.e., a Kevlar hydrogel solution with a Kevlar concentration of 2wt%) is prepared as follows: 2g of KOH solid is added to a 200ml reagent bottle, and then 2ml of DI water, 2g of Kevlar wire, and 95ml of DMSO are added, and magnetic stirring is performed at room temperature for more than 24h.

[0040] Example 1

[0041] The preparation method of the hydrogel photothermal material based on the 3D printing template in this embodiment includes the following steps:

[0042] (1) Pour a completely dissolved Kevlar solution (Kevlar concentration is 2 wt %, the same below) onto a template with a concave radius of 1 mm, and use a scraper to scrape off the excess solution to obtain a Kevlar hydrogel film prototype;

[0043] (2) The Kevlar hydrogel film prototype was completely immersed in pure water for 30 minutes so that it was completely in contact with water and gradually phase-transformed and solidified into a film;

[0044] (3) Carefully peeling the solidified Kevlar hydrogel film from the template to obtain a complete Kevlar hydrogel film with a surface hemispherical microstructure;

[0045] (4) The Kevlar hydrogel film obtained in step (3) is placed in an oxidation solution for oxidation modification to obtain a Kevlar hydrogel film that can be used as a photothermal material. The oxidation solution is a combined solution of m-phenylenediamine (MPD) solution and copper sulfate solution (the same below), the mass fraction of MPD solution and CuSO4 solution are both 5%, and the volume ratio of the two solutions added is 2:1.

[0046] The sample before oxidation modification obtained in step (3) and the sample after oxidation modification obtained in step (4) were respectively subjected to scanning electron microscopy. The results are as follows: Figure 2 As shown, it can be clearly seen that the surface roughness of the Kevlar film after oxidation modification increases, and a PmPD polymer load is formed on the surface, which increases its specific surface area and can further improve the light absorption area of ​​the material.

[0047] In addition, the sample obtained in step (3) of this example is recorded as "HS without oxidation", and the sample obtained in step (4) is recorded as "HS".

[0048] Example 2

[0049] The preparation method of the hydrogel photothermal material based on the 3D printing template in this embodiment includes the following steps:

[0050] (1) Pour the completely dissolved Kevlar solution onto a template with a concave radius of 1 mm, and use a scraper to scrape off the excess solution to obtain a Kevlar hydrogel film prototype;

[0051] (2) The Kevlar hydrogel film prototype was completely immersed in pure water for 30 minutes so that it was completely in contact with water and gradually phase-transformed and solidified into a film;

[0052] (3) Carefully peeling the solidified Kevlar hydrogel film from the template to obtain a complete Kevlar hydrogel film with a surface hemispherical microstructure;

[0053] (4) The Kevlar hydrogel film obtained in step (3) is placed in an oxidizing solution for oxidation modification to obtain a Kevlar hydrogel film that can be used as a photothermal material. The mass fractions of the MPD solution and the CuSO4 solution are 5% and 1%, respectively, and the volume ratio of the two solutions is 2:1.

[0054] Example 3

[0055] The preparation method of the hydrogel photothermal material based on the 3D printing template in this embodiment includes the following steps:

[0056] (1) Pour the completely dissolved Kevlar solution onto a template with a concave radius of 1 mm, and use a scraper to scrape off the excess solution to obtain a Kevlar hydrogel film prototype;

[0057] (2) The Kevlar hydrogel film prototype was completely immersed in pure water for 30 minutes so that it was completely in contact with water and gradually phase-transformed and solidified into a film;

[0058] (3) Carefully peeling the solidified Kevlar hydrogel film from the template to obtain a complete Kevlar hydrogel film with a surface hemispherical microstructure;

[0059] (4) The Kevlar hydrogel film obtained in step (3) is placed in an oxidizing solution for oxidation modification to obtain a Kevlar hydrogel film that can be used as a photothermal material. The mass fractions of the MPD and CuSO4 solutions are 1% and 5% respectively, and the volume ratio of the two solutions is 2:1.

[0060] Example 4

[0061] The preparation method of the hydrogel photothermal material based on the 3D printing template in this embodiment includes the following steps:

[0062] (1) Pour the completely dissolved Kevlar solution onto a template with a concave radius of 0.5 mm, and use a scraper to scrape off the excess solution to obtain a Kevlar hydrogel film prototype;

[0063] (2) The Kevlar hydrogel film prototype was completely immersed in pure water for 30 minutes so that it was completely in contact with water and gradually phase-transformed and solidified into a film;

[0064] (3) Carefully peeling the solidified Kevlar hydrogel film from the template to obtain a complete Kevlar hydrogel film with a surface hemispherical microstructure;

[0065] (4) The Kevlar hydrogel film obtained in step (3) is placed in an oxidation solution for oxidation modification to obtain a Kevlar hydrogel film that can be used as a photothermal material. The oxidation solution is a combined solution of m-phenylenediamine (MPD) solution and copper sulfate solution, the mass fraction of the MPD solution and the CuSO4 solution are both 5%, and the volume ratio of the two solutions added is 2:1.

[0066] Comparative Example 1

[0067] This comparative example adopts a flat structure template (without a recessed array structure), and specifically includes the following steps:

[0068] (1) Pour a completely dissolved Kevlar solution (the Kevlar concentration is also 2 wt%) onto the template, and use a scraper to scrape off the excess solution to obtain a Kevlar hydrogel film prototype;

[0069] (2) The Kevlar hydrogel film prototype was completely immersed in pure water for 30 minutes so that it was completely in contact with water and gradually phase-transformed and solidified into a film;

[0070] (3) peeling the solidified Kevlar hydrogel film from the template to obtain a complete Kevlar hydrogel film with a flat structure;

[0071] (4) The Kevlar hydrogel film obtained in step (3) is placed in an oxidation solution for oxidation modification to obtain a Kevlar hydrogel film that can be used as a photothermal material. The oxidation solution is a combined solution of m-phenylenediamine (MPD) solution and copper sulfate solution (the same below), the mass fraction of MPD solution and CuSO4 solution are both 5%, and the volume ratio of the two solutions added is 2:1.

[0072] In addition, the sample obtained in step (3) of this comparative example is recorded as "FS without oxidation", and the sample obtained in step (4) is recorded as "FS".

[0073] Performance Testing

[0074] The samples "HS without oxidation" and "HS" obtained in Example 1 and the samples "FS without oxidation" and "FS" obtained in Comparative Example 1 were subjected to an experiment of evaporating pure water and sodium chloride solution under a 1-sun light intensity. The experimental results are as follows: Figure 3 shown.

[0075] In addition, based on the method of the present invention, the inventors also studied the effects of oxidation solutions with different MPD concentrations and different CuSO4 solution concentration ratios on the products. The ratio of the amount of MPD solution and CuSO4 solution in the oxidation solution was fixed at 2:1 (volume ratio), and the surface element specific gravity results of the XPS test of the obtained samples are shown in Table 1. Moreover, unlike the oxidation solutions currently used in the membrane separation field, which require H2O2 as the third component in addition to the MPD component and the CuSO4 component, the present invention can achieve a good oxidation effect using only the two components of MPD and CuSO4, and has good performance in the field of photothermal materials.

[0076] Table 1

[0077]

[0078]

[0079] The above embodiment takes a mold having a hemispherical array structure of depressions on its surface as an example. The specific shape of the depression units may be other shapes besides hemispherical, such as polygonal columns, polygonal pyramids, etc.

[0080] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrogel photothermal material, characterized in that: The following steps are involved: (1) pouring a completely dissolved Kevlar hydrogel solution onto a template and leveling it to obtain a Kevlar hydrogel film prototype; wherein the surface of the template has a concave array structure; after leveling, the thickness of the hydrogel solution left on the template is 100-1000 μm; (2) soaking the Kevlar hydrogel film prototype in pure water so that it is completely in contact with water and gradually undergoes phase transformation and solidifies into a film; (3) peeling the solidified Kevlar hydrogel film from the template to obtain a Kevlar hydrogel film having a corresponding protrusion array structure on the surface; (4) placing the Kevlar hydrogel film obtained in step (3) into an oxidizing solution for oxidative modification, thereby obtaining an oxidatively modified Kevlar hydrogel film, which is a hydrogel photothermal material; wherein the oxidizing solution is a mixed aqueous solution of copper sulfate and metaphenylenediamine (MPD); In the step (4), the oxidizing solution is obtained by mixing an aqueous solution of m-phenylenediamine and an aqueous solution of copper sulfate; wherein the mass percentage concentration of the aqueous solution of m-phenylenediamine is 1-10%, and the mass percentage concentration of the aqueous solution of copper sulfate is 1-10%; The mixing is carried out in a volume ratio of 1-10:1 between the m-phenylenediamine aqueous solution and the copper sulfate aqueous solution.

2. The method for preparing the hydrogel photothermal material according to claim 1, characterized in that: In the step (4), the time for oxidative modification in the oxidative solution is 10-30 minutes.

3. The method for preparing the hydrogel photothermal material according to claim 1, characterized in that: In the step (1), the template is obtained by 3D printing, and the material of the template is an alloy; the mass percentage concentration of the Kevlar hydrogel solution is 0.1-2%; In the step (2), the soaking time is 10-60 minutes.

4. The method for preparing the hydrogel photothermal material according to claim 1, characterized in that: In the step (1), the Kevlar hydrogel solution is obtained by dissolving Kevlar fibers in a mixed solution of KOH aqueous solution and DMSO; In the step (1), the leveling is specifically performed by scraping off excess solution using a scraper.

5. The method for preparing the hydrogel photothermal material according to claim 1, characterized in that: In the step (1), the projection size of a single recessed array structure unit on the template surface onto the plane where the template surface is located is 0.5-2 mm.

6. The method for preparing the hydrogel photothermal material according to claim 5, characterized in that: In the step (1), the surface of the template has a recessed hemispherical array structure; the projection of a single recessed hemispherical array structure unit on the plane where the template surface is located is a circle, and the diameter of the circle is 0.5-2 mm; accordingly, the Kevlar hydrogel film obtained in the step (3) is a Kevlar hydrogel film with a hemispherical protrusion array structure on the surface.

7. The hydrogel photothermal material prepared by the method according to any one of claims 1 to 6.

8. Use of the hydrogel photothermal material as claimed in claim 7 as a photothermal material.

9. The use according to claim 8, characterized in that The application is specifically the application in photothermal evaporation using light energy; wherein the light energy is solar energy.

10. The use according to claim 9, characterized in that: The photothermal evaporation is specifically used for seawater desalination or high-salinity wastewater treatment.

Citation Information

Patent Citations

  • Photo-thermal film and preparation method and application thereof

    CN113603913A

  • Method for shape representation of hydrogel micro-pore arrays

    CN103913601A

  • Kevlar nanofiber composite forward osmosis membrane, and preparation method and application thereof

    CN104548968A